KEEFEKTIFAN PROGRAM IMUNISASI DALAM PENDIDIKAN KESEHATAN SEKOLAH - Upus Piatun Khodijah; Muspian (CV. Adiba Aisha Amira, 2025)
The eflectiveness of immunisation programmes in school health education refers to the degree of success and positive impact resulting from the integration of immunisation services into the health education system in the school setting. This includes the ability of the programme to achieve specific goals, such as increasing vaccination coverage among students, reducing the incidence of vaccine-preventable diseases, and increasing knowledge and awareness about immunisation in the school community. The programme is considered eflective when it can deliver significant and measurable benefits in the context of public health, while maximising the use of available resources. Furthermore, the eflectiveness of immunisation programmes in school health education also involves aspects such as accessibility of services, acceptance by students and parents, seamless integration with the school curriculum, and long-term sustainability. Eflective programmes not only focus on vaccine delivery, but also create an enabling environment for comprehensive health education, build strong partnerships between the education and health sectors, and facilitate positive behaviour change related to immunisation and other preventive health practices. As such, the eflectiveness of these programmes is measured not only by direct health outcomes, but also by their impact on the education and health system as a whole.